An integrated Terrestrial Laser Scanner (TLS), Deviation Analysis (DA) and Finite Element (FE) approach for health assessment of historical structures. A minaret case study. (15th December 2017) - Korumaz, Mustafa; Betti, Michele; Conti, Alessandro; Tucci, Grazia; Bartoli, Gianni; Bonora, Valentina; Korumaz, Armağan Güleç; Fiorini, Lidia
Highlights: Interdisciplinary approach between architectural and structural surveying. 3D modelling issue as an important intersection between two complementary disciplines. Filling the gap between FE structural analysis and TLS technology. Abstract: This paper presents a multi-disciplinary approach for identification of historic buildings structural health with combination of Terrestrial Laser Scanning (TLS) survey, Deviation Analysis (DA) and Finite Element (FE) numerical modelling. The proposed methodology was discussed through the application to an illustrative case study: an early medieval period brick minaret (Eğri Minaret) located in Aksaray (central Turkey). After standing upright for several centuries, the minaret has developed tilt, and today the structure is supported with steel cables. Precise direction of inclination, leaning angle, local deviations from circular building shape, deflections from vertical planes, local curvatures and related maps were obtained with high accuracy by DA, based on detailed point cloud 3D mesh model. Differently from traditional approaches in FE analysis, the paper discusses a method for direct transfer of high accuracy TLS based 3D model to FE structural analysis software, subsequently employed to interpret and verify structural health of the historic building. Through the discussion of the results, it can be considered that the integration of these different techniques (being the whole process non-destructive, effective and expeditious for surface analysis) is a promising methodology for health assessment and analysis of historic constructions.